1998
DOI: 10.1046/j.1523-5378.1998.08018.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H. pylori Infection and CagA Status on Leukocyte Counts and Liver Function Tests: Extra‐Gastric Manifestations of H. pylori Infection

Abstract: We confirmed an increase in total leukocyte count and number of polymorphonuclear leukocytes in those with H. pylori infection. We also confirmed higher SGOT levels with CagA-positive H. pylori infection, but the failure to resolve within 3 months of cure of the infection makes it unlikely to be a direct result of the H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…Helicobacterpositive patients had higher levels of aspartate aminotransferase and similar levels of alanine transaminase, alkaline phosphatase, and total bilirubin compared with the Helicobacter-negative group, whereas 2 studies in the literature found increased alkaline phosphatase and alanine transaminase in patients with H pylori infection [9,22]. Our results may differ from those in the literature due to the late stage of disease present in our study population.…”
Section: Discussioncontrasting
confidence: 73%
“…Helicobacterpositive patients had higher levels of aspartate aminotransferase and similar levels of alanine transaminase, alkaline phosphatase, and total bilirubin compared with the Helicobacter-negative group, whereas 2 studies in the literature found increased alkaline phosphatase and alanine transaminase in patients with H pylori infection [9,22]. Our results may differ from those in the literature due to the late stage of disease present in our study population.…”
Section: Discussioncontrasting
confidence: 73%
“…A possible role for HP in osteoporosis has been suggested due to the fact that HP infection may induce chronic low level systemic inflammatory status. Inflammatory markers such as TNFalpha and IL-6 have roles in bone metabolism 14,21) . TNFalpha increases bone resorption, and IL-6 raises the number of osteoclasts 2) .…”
Section: Discussionmentioning
confidence: 99%
“…Two possible explanations could account for the observed findings: the inflammatory response to the infection and the existence of cross-mimicry phenomena between H. pylori and sperm antigens. The humoral and cellular immune responses to the invading organisms increase the local and systemic indices of inflammation, such as the levels of polymorphs and monocytes [18]. The colonized gastric epithelium and immunocytes stimulated by the bacterial determinants of pathogenicity secrete vasoactive substances and cellular mediators, such as cytokines.…”
Section: Discussionmentioning
confidence: 99%